Non-invasive Autonomic Neuromodulation Is Opening New Landscapes for Cardiovascular Diseases - Chen, Mingxian; Wang, Songyun; Li, Xuping; Yu, Lilei; Yang, Hui; Liu, Qiming; Tang, Jianjun; Zhou, Shenghua (Frontiers in Physiology, 2020)
Autonomic imbalance plays a crucial role in the genesis and maintenance of cardiac disorders. Neuromodulation, mostly designed to keep the autonomic nervous system (ANS) balance, has been an emerging therapeutic approach to treat these kinds of heart diseases. However, neuromodulations including direct electrical stimulation or denervation have to invasively implant a generator and a bipolar electrode subcutaneously, or autonomic nervous damage, inevitably increasing the risk of complications. More recently, non-invasive neuromadulations have been so far received great interest in ANS modulation. Non-invasive approaches have open new field in the treatment of cardiovascular diseases. Herein, we will review the protective roles of non-invasive modulation techniques in heart diseases, including tragus nerve stimulation, electromagnetic field, ultrasound stimulation, autonomic stimulation in optogenetics, light emitting diode and transcutaneous cervical vagus nerve stimulation (gammaCore).